Le pagne traditionnel raphia en pays dida et godié : expression cosmogonique ou vision symbolique - Soumaϊla FOFANA (Revue Hybrides)
Traditional African plastic creations are largely the fruit of the world vision of the initiating peoples. They are also the expression of daily life. We find this symbolic language as well in sculptural works as in ceramics, textiles, etc. The plastic productions of the Dida and Godié peoples in general and their traditional raffia loincloth in particular are no exception to this rule. Whatever its artistic value linked to the beauty of the patterns, colors and its material, this loincloth remains and remains a cultural and social product which finds its foundation in the cosmogony of the people who use it during important moments of their existence. The stylized drawings which appear there either in association or alternately, are intimately linked to societal life. They have special meanings. From then on, the raffia loincloth, in addition to being a support for expression and communication, constitutes the identity and reflection of the mirror of Dida and Godié culture. Thus, to carry out this study, it was necessary to carry out field investigations in order to see the artists or craftsmen at work through visits to production workshops to understand the manufacturing process of this loincloth, the meaning colors and patterns that animate it. This approach obviously makes it possible to determine the production techniques of this loincloth. This study is a window which presents the traditional raffia loincloth as a cultural and symbolic object which takes its source in the cosmogony of the peoples chosen for the study.